Maize leaf epiphytic bacteria diversity patterns are genetically correlated with resistance to fungal pathogen infection - Balint Kurti, Peter (2010)
Plant leaves host a specific set of microbial epiphytes. Plant genetic and solar UV-B radiation effects on the diversity of the phyllosphere were examined by measuring epiphytic bacterial ribosomal DNA diversity in a maize recombinant inbred (RI) mapping population. Several chromosomal quantitative trait loci (QTL) with significant effects on bacterial diversity were identified, some of which had effects only in the presence of UV-B radiation and others that had effects both with and without UV-B. Candidate genes with allele-specific effects were mapped to the bacterial diversity chromosomal regions. A glutamate decarboxylase candidate gene was located at a UV-B-specific chromosomal locus, and in a comparison between two RI lines with contrasting bacterial diversity phenotypes, high bacterial diversity was associated with high levels of glutamate decarboxylase enzyme activity, a component of the gamma-aminobutyric acid (GABA) pathway. The bacterial diversity loci exhibited a significant overlap with loci connected with Southern leaf blight (SLB) susceptibility in the field. A SLB-resistant inbred genotype had less beta bacterial diversity, and antibiotic treatment of inbreds increased this diversity. These results suggest that the GABA pathway is genetically associated with phyllosphere bacterial diversity. Furthermore, the colocalization of QTL between low bacterial diversity and fungal blight-resistance and the increase in beta diversity in antibiotic-treated leaves suggest that occupation of leaf habitats by a particular set of suppressive bacteria may restrict phyllosphere bacterial variability and increase resistance to fungal infection. © 2010 The American Phytopathological Society.